Social Connectivity and Educational Inclusion Among Disabled Individuals - Eddine, Belouadah Ahmed Seif; Mendonca, Cipriano Nunes; Seran, Gregorius (Journal of Social Science Studies, 2024)
This paper investigates how internal social relations within disabled communities influence access to and engagement with educational opportunities. Through a comprehensive literature-based analysis, the study identifies key relational mechanisms such as peer support, collective identity, informal mentorship, and cultural discourse that enable or hinder participation in educational systems. The findings reveal that relational networks function as both sources of resilience and potential sites of fragmentation, significantly affecting motivation, institutional navigation, and help-seeking behavior. Empowering community discourses enhance self-efficacy and persistence, while internalized stigma and fragmented alliances may suppress educational aspirations. Digital interaction, disclosure norms, and intersectional identities further shape access, producing a diverse landscape of relational influence. The paper argues that educational access must be understood not solely through institutional metrics or policy compliance, but through the emotional, cultural, and political textures of everyday life within disabled populations. By shifting focus toward the epistemic and structural role of community dynamics, this study contributes to a more comprehensive understanding of inclusive education. It recommends greater attention to intra-community engagement in research, policy formation, and program design. The analysis affirms the critical need to recognize social relations not as auxiliary, but as constitutive of how education is sought, experienced, and sustained.